Outcome differences in acute vs. acute on chronic heart failure and cardiogenic shock - Tara L. Jones; Michael C. Tan; Vidang Nguyen; Kathleen E. Kearney; Charles C. Maynard; Emily Anderson; Claudius Mahr; James M. McCabe (ESC Heart Failure)
Abstract Aims Despite advances in coronary reperfusion and percutaneous mechanical circulatory support, mortality among patients presenting with cardiogenic shock (CS) remains unacceptably high. Clinical trials and risk stratification tools have largely focused on acute CS, particularly secondary to acute coronary syndrome. Considerably less is understood about CS in the setting of acute decompensation in patients with chronic heart failure (HF). We sought to compare outcomes between patients with acute CS and patients with acute on chronic decompensated HF presenting with laboratory and haemodynamic features consistent with CS. Methods and results Sequential patients admitted with CS at a single quaternary centre between January 2014 and August 2017 were identified. Acute on chronic CS was defined by having a prior diagnosis of HF. Initial haemodynamic and laboratory data were collected for analysis. The primary outcome was in‐hospital mortality. Secondary outcomes were use of temporary mechanical circulatory support, durable ventricular assist device implantation, total artificial heart implantation, or heart transplantation. Comparison of continuous variables was performed using Student's t‐test. For categorical variables, the χ2 statistic was used. A total of 235 patients were identified: 51 patients (32.8%) had acute CS, and 184 patients (64.3%) had acute decompensation of chronic HF with no differences in age (52 ± 22 vs. 55 ± 14 years, P = 0.28) or gender (26% vs. 23%, P = 0.75) between the two groups. Patients with acute CS were more likely to suffer in‐hospital death (31.4% vs. 9.8%, P < 0.01) despite higher usage of temporary mechanical circulatory support (52% vs. 25%, P < 0.01) compared with patients presenting with acute on chronic HF. The only clinically significant haemodynamic differences at admission were a higher heart rate (101 ± 29 vs. 82 ± 17 b.p.m., P < 0.01) and wider pulse pressure (34 ± 19 vs. 29 ± 10 mmHg, P < 0.01) in the acute CS group. There were no significant differences in degree of shock based on commonly used CS parameters including mean arterial pressure (72 ± 12 vs. 74 ± 10 mmHg, P = 0.23), cardiac output (3.9 ± 1.2 vs. 3.8 ± 1.2 L/min, P = 0.70), or cardiac power index (0.32 ± 0.09 vs. 0.30 ± 0.09 W/m2, P = 0.24) between the two groups. Conclusions Current definitions and risk stratification models for CS based on clinical trials performed in the setting of acute coronary syndrome may not accurately reflect CS in patients with acute on chronic HF. Further investigation into CS in patients with acute on chronic HF is warranted.